Effect of different protocols on the mitigation of exercise‐induced pulmonary hemorrhage in horses when administered 24 hours before strenuous exercise - Warwick Bayly; Carolina Lopez; Raymond Sides; Gerald Bergsma; Jenyka Bergsma; Jenifer Gold; Debra Sellon (Journal of Veterinary Internal Medicine, 2019)
Abstract Background Public pressure exists in the United States to eliminate race‐day furosemide administration despite its efficacy in decreasing the severity of equine exercise pulmonary hemorrhage (EIPH). No effective alternative prophylaxis strategies have been identified. Objective To investigate alternative protocols to race‐day furosemide that might mitigate EIPH. Animals Seven fit Thoroughbreds with recent EIPH. Methods Double‐blinded placebo‐controlled Latin square crossover using a treadmill followed by a blinded placebo‐controlled crossover study at a racetrack. First, horses exercised supramaximally to fatigue 24 hours after initiating 5 EIPH prophylaxis protocols: 0.5 and 1.0 mg/kg furosemide IV 24 hours pre‐exercise with and without controlled access to water, and 24 hour controlled access to water. Effects were compared to those measured after giving a placebo 24 hours pre‐exercise, and 0.5 mg/kg furosemide IV 4 hours pre‐exercise. Bronchoalveolar lavage (BAL) erythrocyte count was determined 45‐60 minutes postexercise after endoscopy to assign an EIPH score. Data were analyzed using linear mixed effects models. The most promising protocol from the treadmill study was further evaluated in 6 horses using endoscopy and BAL after 1100 m simulated races. Results Intravenous furosemide (0.5 mg/kg) administered 24 hours pre‐exercise combined with controlled access to water decreased the severity of EIPH on the treadmill and at the racetrack. Conclusion and Clinical Importance Administering 0.5 mg/kg furosemide 24 hours pre‐racing combined with controlling water intake may be a strategy to replace race‐day furosemide administration for the management of EIPH. A larger study is indicated to further evaluate whether this protocol significantly mitigates EIPH severity.